Chikungunya fever in the Emilia Romagna region: what is the public health message? (Italian Journal of Public Health, 2009)
Introduction Chikungunya virus (CHIKV) is a mosquitoborne alphavirus indigenous to African countries, the Indian Subcontinent, and Southeast Asia, where it causes endemic and epidemic chikungunya (CHIK) fever [1]. Chikungunya infection is transmitted by biting mosquitoes belonging to the genus Aedes. Since the identification of the virus in the 1950s [2] in Africa, transmission to humans has been usually associated with bites of A. aegypti mosquitoes. In recent outbreaks occurring in the South-eastern islands of the Indian Ocean, transmission has also been associated with A. albopictus, also known as the “tiger mosquito.” This species is indigenous to Southeast Asia, the Western Pacific, and the Indian Ocean, but has recently spread to Africa, the Middle East, Europe, and the Americas. [3]. Although tropical forests are considered to be their original habitat, A. aegypti and A. albopictus have developed the capacity to exploit artificial environments [4]. Besides the natural habitat consisting of tree holes filled with water and other small natural pools, they are capable of breeding in any artificial habitat with small reservoirs of stagnant water, such as vases, buckets, tires and other containers found around houses in urban and periurban areas.
Keywords: Chikungunya; Italy; outbreak; Public health